The Therapeutic Effects and Possible Mechanism of Pranoprofen in Mouse Model of Corneal Alkali Burns - Minting Chen; Abdirahman Abdinasir Gureeye; Yacouba Cissé; Lang Bai (Journal of Ophthalmology)
Objective. To investigate therapeutic effects and possible mechanism of pranoprofen in a mouse model of corneal alkali burns and provide new evidence for the clinical treatment of corneal alkali burns. Methods. A unilateral alkali burn was created in the central cornea by placing a piece of 2 mm diameter filter paper soaked in 1N NaOH on the right eye for 30 seconds. After the model was performed, C57BL/6J mice received topical treatment with saline eye drops or pranoprofen eye drops and were, respectively, categorized as saline group and pranoprofen group, whereas the remaining normal mice that were not subjected to alkali burns served as control, each group containing 15 mice (n = 45). On the 5th day after model establishment, the corneal fluorescein sodium staining score was evaluated in order to assess corneal epithelial damage. Tissue HE stain was used to observe the pathological changes of corneal tissue in each group. Real-time RT-PCR and western blot were also performed to detect the mRNA and protein expression of NLRP3, IL-1β/p17, and matrix metallopeptidase MMP-13. Results. 5 days after burns, microscopic observations of the pranoprofen group showed less corneal opacity and neovascularization development than the saline group. Sodium fluorescein staining showed obvious corneal structure disorders, poor corneal epithelium continuity, and a larger corneal epithelial defect area in the saline group (10.33±+−0.57) as opposed to the pranoprofen group (8.33 ± 0.57） (p<0.05). HE stain results showed the saline group had obvious corneal structure disorder and the corneal epithelial layer was incomplete as opposed to the pranoprofen group. PCR and western blot results suggested that the pranoprofen group expressed less NLRP3, IL-1β, and MMP-13 mRNA and protein expression in corneal tissue than the saline group (p<0.05). Conclusion. Pranoprofen may alleviate inflammatory response by inhibiting the expression levels of NLRP3 and IL-1β at the early stage of corneal alkali injury, lowering the expression of MMP-13 and ultimately reducing corneal epithelial damage.